A Christian perspective of contemporary nudity: Theological and ethical reflections on symbolic nakedness. - Rode, Susan L. (University of Ottawa (Canada), 2000)
This thesis represents and records the results of investigations in the area of contemporary nudity in North American society and the meanings attached and applied to human nakedness by our culture. We wanted to uncover and reveal why human nakedness seems to be considered only in connection with sexuality and given mostly negative interpretations. We identified a symbolic paradigm of nudity at work within both society and Christian discourse, a paradigm which connects human nakedness to fallen humanity, usually represented by references to Adam and Eve. This tie or relationship appears to lead to negative constructs of nudity, to interpretations of nakedness which communicate a sexuality considered only in a negative fashion. We have coined the phrase---"the Adam and Eve (Adam/Eve) connection"---to clarify, indicate and identify this joining of contemporary nudity to the Genesis couple. The thesis looks to Christian tradition in an attempt to retrieve some basis for an alternate model, a model which would specifically connect our nudity to Christ and in this way symbolically reflect our redeemed nature as well as our fallen state. We expressed such a relationship or tie with the phrase---"the Christ connection". Inspired by the research on nudity conducted by ethicist Andre Guindon and the theory of symbolism developed by theologian Paul Tillich, we turned to early baptismal texts and Christian iconography. Guindon's bold and innovative work on nudity and the Christian faith guides our own investigations and frames our discussions. Tillich's symbolic theory has influenced and been implemented by many researchers in various disciplines and seems especially appropriate for investigations into nudity as a symbol within our North American culture. An examination of the second baptismal catechesis of Cyril of Jerusalem and Renaissance images of the naked Christ as documented by Leo Steinberg, enabled us to construct a Christocentric symbolic paradigm. This paradigm indicates and provides meanings of Christ's symbolic nudity. The baptismal instructions given by Cyril explicates and clarifies the connection between the initiate and Christ, a relationship which Cyril indicates with the use of nudity as a symbol. The connection between the believer and Christ is symbolized and actualized by the nudity of both. Nudity forms the symbolic bond connecting Christ and the neophyte. Steinberg's exploration of theological meanings communicated by artistic imagery of the naked Christ, led us to delinate meanings and interpretations of the symbolic nudity of Christ. These meanings were then applied in a new model which was employed to offer constructive, positive meanings of human nudity. Finally, we indicated theological and ethical implications of the implementation of this Christocentric paradigm. Such a model presents nudity in a positive fashion because it indicates and reveals our graced relationship with and in the risen Christ. In the light of our new model, human nakedness may be considered as a positive, affirming symbol (nudity). (Abstract shortened by UMI.)
Keywords: Theology.